Federated Learning Meets Contract Theory: Economic-Efficiency Framework for Electric Vehicle Networks - Saputra, Yuris Mulya; Nguyen, Diep N.; Hoang, Dinh Thai; X. Vu, Thang; Dutkiewicz, Eryk; Chatzinotas, Symeon (Institute of Electrical and Electronics Engineers Inc., 2022)
In this paper, we propose a novel economic-efficiency framework for an electric vehicle (EV) network to maximize the profits (i.e., the amount of money that can be earned) for charging stations (CSs). To that end, we first introduce an energy demand prediction method for CSs leveraging federated learning approaches, in which each CS can train its own energy transactions locally and exchange its learned model with other CSs to improve the learning quality while protecting the CS's information privacy. Based on the predicted energy demands, each CS can reserve energy from the smart grid provider (SGP) in advance to optimize its profit. Nonetheless, due to the competition among the CSs as well as unknown information from the SGP, i.e., the willingness to transfer energy, we develop a multi-principal one-agent (MPOA) contract-based method to address these issues. In particular, we formulate the CSs' profit maximization as a non-collaborative energy contract problem under the SGP's unknown information and common constraints as well as other CSs' contracts. To solve this problem, we transform it into an equivalent low-complexity optimization problem and develop an iterative algorithm to find the optimal contracts for the CSs. Through simulation results using a real CS dataset, we demonstrate that our proposed framework can enhance energy demand prediction accuracy up to 24.63 percent compared with other machine learning algorithms. Furthermore, our proposed framework can outperform other economic models by 48 and 36 percent in terms of the CSs' utilities and social welfare (i.e., the total profits of all participating entities) of the network, respectively.